Observability and controllability analysis for sandwich systems with backlash - Luo, Na; Tan, Yonghong; Dong, Ruili (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, an approach to analyze the observability and controllability of sandwich systems with backlash is proposed. In this method, a non-smooth state-space function is used to describe the sandwich systems with backlash which are also non-smooth non-linear systems.
Keywords: backlash; sandwich systems; non-smooth systems; state-space equations; observability; controllability